2004
DOI: 10.2172/918295
|View full text |Cite
|
Sign up to set email alerts
|

Blade system design studies volume II : preliminary blade designs and recommended test matrix.

Abstract: As part of the U.S. Department of Energy's Wind Partnerships for Advanced Component Technologies (WindPACT) program, Global Energy Concepts, LLC is performing a Blade System Design Study (BSDS) concerning innovations in materials, processes and structural configurations for application to wind turbine blades in the multi-megawatt range. The BSDS Volume I project report addresses issues and constraints identified to scaling conventional blade designs to the megawatt size range, and evaluated candidate materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In 2002 SNL initiated a research program [14,15] to demonstrate the use of carbon fiber in subscale blades and investigate innovative concepts through the WindPACT Blade System Design Studies (BSDS) via design studies and prototype fabrications [16,17,18]. Three 9-m designs were created with assistance from Global Energy Systems Consulting (GEC), Dynamic Design Engineering, and MDZ Consulting; and seven blades from each design were manufactured by TPI Composites.…”
Section: Tx-100 Bladementioning
confidence: 99%
“…In 2002 SNL initiated a research program [14,15] to demonstrate the use of carbon fiber in subscale blades and investigate innovative concepts through the WindPACT Blade System Design Studies (BSDS) via design studies and prototype fabrications [16,17,18]. Three 9-m designs were created with assistance from Global Energy Systems Consulting (GEC), Dynamic Design Engineering, and MDZ Consulting; and seven blades from each design were manufactured by TPI Composites.…”
Section: Tx-100 Bladementioning
confidence: 99%
“…In a European research effort, carbon fiber composites were investigated for potential improvements in blade weight and cost [1][2][3][4]. Under the Global Energy Concepts, LLC (GEC)/Sandia Blade System Design Study, carbon fiber material was identified as cost effective for use in the load bearing spar structure [5,6]. Both of these studies show moderate promise for economic use of carbon in turbine blades, with the additional benefits of decreased weight and increased blade stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…At present, all-carbon fiber is prohibitively expensive for multimegawatt scale HAWT blades [27]. Carbon fiber is more expensive than glass fiber, so that it is only used in certain locations, e.g.…”
Section: Blade Weight Challengementioning
confidence: 99%